Perancangan Sistem Rekap Berbasis Web Menggunakan Framework Laravel Di Dinas Tenaga Kerja Kota Samarinda - Dio Ferdinan; Adhis Prasetyo; Muhammad Ghozi Alghifari Sholihuddin; Muhammad Alviansyah; Reza Oktavian Noor; Arbansyah (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
The design of the Web-Based Recap System is a strategic step in addressing issues related to data management and information efficiency that occur at the Samarinda Manpower Office. The focus of this service is centered on developing a system that facilitates the recapitulation process of labor-related data. The main purpose of this service is to provide technological solutions that facilitate the management of labor data and improve information transparency at the Samarinda City Manpower Office. The research method adopted involves a survey of user needs, an in-depth analysis of the recap process, as well as the application of the Laravel Framework to build a responsive and accessible web platform.